Control of the body and narrative: interpretative semiotic analysis of the autobiographical work Platonic Sex - Benavides Torres, Evelin Nataly (SATHIRI, 2025)
In this article, the autobiographical story Platonic Sex by Ai Ijima will be analyzed from the perspective of interpretive semiotics (2004), in which we find ideological aspects, social conventions, discursive practices, traditions, norms and values that revolve mainly around the narrative of the body as a space of control and social power. This article is based on a theoretical approach to the interpretative semiotic analysis of the linguistic signs of the work, where the encounter of an actor with the values of the cultural system of the Japanese community in the nineties and in the beginning of the two thousand is made possible. The aim of this proposal is to analyze and interpret how Ai Ijima's narrative is a framework , which the meaning of a social phenomenon is produced, interpreted and communicated. In this work, it is evident how a woman's body, while objectified and manipulated by a lucrative sex industry, is also a motive for contempt and rejection by a society that values women for fulfilling social norms and expectations.
Keywords: semiotic analysis; body; autobiography; semiotics; japanese society